Edukasi ASI Eksklusif Melalui WhatsApp Group dan Pendampingan pada Tujuh Hari Pertama Kelahiran - Wahidah Sukriani; Noordiati Noordiati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The first days of birth are a vulnerable period for babies to be given prelactal food by mothers or families. Exclusive breastfeeding was associated with various factors, including media exposure. Social media such as WhatsApp is a new communication method for Health Education. Mothers exposed to media such as WhatsApp Groups have a greater opportunity to give exclusive breastfeeding. This community service aimed to increase the knowledge of pregnant women about exclusive breastfeeding and increased breastfeeding rates in Palangka Raya City. We used WhatsApp Groups as a medium for providing information about exclusive breastfeeding. Participants in the activity were carried out pretest before and posttest, after the activity was carried out and mentoring was carried out for seven days after birth. There was an increase in knowledge of the activity participants after providing information through WhatsApp Groups, and 70% of participants successfully gave their babies just mother’s milk for seven days after delivery. Health workers can use WhatsApp for providing health information, especially during the covid-19 pandemic.